Suggested Utilization of Resources and Guide for Expenditures. Guidelines for Identifying, Classifying, and Serving the Disadvantaged and Handicapped Under the Vocational Education Amendments of 1968 - Office of Education (DHEW), Washington, DC.; Office of Education (DHEW), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
To serve as a basis for establishing compatibility among the states in planning, implementing, and evaluating programs and services for persons with special needs and in reporting enrollments and other pertinent information, this pamphlet provides specific requirements of the Vocational Education Amendments of 1968, and classification systems for identifying the disadvantaged and handicapped. These guidelines will prove useful for teachers and other educators in helping these groups to pursue careers successfully. A bibliography and six sample tabular forms for reporting statistical data are included. This working document is a revised edition of a 1970 pamphlet of the same title. (AG)
ERIC Note: Revision.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Development; Classification; Disabilities; Disadvantaged; Expenditures; Federal Legislation; Guidelines; Human Services; Identification; Program Development; Resource Allocation; Vocational Education; Vocational Education Amendments 1968